2019
DOI: 10.2217/bmm-2019-0183
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Presepsin in the Diagnosis of Chronic Obstructive Pulmonary Disease Acute Exacerbation with Pneumonia

Abstract: Aim: In this study, we aimed to investigate the role of presepsin in detecting concomitant pneumonia in patients presenting with acute exacerbation of chronic obstructive pulmonary disease (COPD) in the emergency department. Patients & methods: Three groups were formed in the study. Group 1: patients diagnosed with acute exacerbation of COPD; group 2: patients with acute exacerbation of COPD + pneumonia; group 3: healthy individuals. Results: Presepsin levels of the patients in group 2 were significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
6
0
3
Order By: Relevance
“…Recently, Halıcı et al reported that presepsin was useful for diagnosing pneumonia in chronic obstructive pulmonary disease patients with acute exacerbations (AUC 0.70) (64). However, the diagnostic accuracy of presepsin was not higher than of PCT (AUC 0.72) and CRP (AUC 0.75) (64).…”
Section: Presepsinmentioning
confidence: 71%
“…Recently, Halıcı et al reported that presepsin was useful for diagnosing pneumonia in chronic obstructive pulmonary disease patients with acute exacerbations (AUC 0.70) (64). However, the diagnostic accuracy of presepsin was not higher than of PCT (AUC 0.72) and CRP (AUC 0.75) (64).…”
Section: Presepsinmentioning
confidence: 71%
“…Higher values of presepsin are associated with septic shock compared to severe sepsis without shock, a trend similar to that observed with PCT [ 1 ]. In probable infections with an identifiable focus, presepsin may be of value in differentiating whether an exacerbation of chronic obstructive pulmonary disease is due to pneumonia or non-infectious in etiology [ 14 ], and may also be useful in patients presenting with nephrolithiasis and systemic inflammatory response syndrome (SIRS) symptoms to rule out pyelonephritis as a cause [ 15 ], and may aid in differentiating between the causes of acute abdomen [ 16 ]. In patients with definite pyelonephritis, a higher presepsin cutoff may be used to test for the presence of bacteremia [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…sepsin does not have lipopolysaccharide binding properties, so it cannot be captured by anti-CD14 antibodies; thus, this free molecule can be used as a biomarker. Numerous studies have shown that presepsin levels are increased in the early stages of bacteremia and sepsis, and presepsin has been proposed as a biomarker for routine use [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%